Atividade Larvicida de Bacillus spp. da Amazônia brasileira portadores dos genes Cry e BSglu (β - Glucanase), no controle de Aedes Aegypti Linnaeus, 1762 - Alves Muniz, Veranilce (2019)
The Aedes aegypti mosquito is a vector of the arboviruses Dengue, Zika and Chikungunya, which cause public health problems in several regions of the world. Vector control is the best way to alleviate this problem, which may be socio-educational, physical, chemical and biological. However, chemicals cause negative impacts on the environment and humans. The use of entomopathogenic microorganisms, mainly bacteria of the genus Bacillus, becomes a promising alternative in the fight against this mosquito. The objective of this study was to select bacteria isolated from Amazonian environments, carrying the Cry and BS-glu genes, with larvicidal potential, to contribute to the control of Ae. aegypti. In this work 21 lines of collections of academic papers were obtained from soils, water, plant and insect from different Amazonian environments. The bacilli strains of this study were submitted to the PCR reaction using the nucleotide sequence encoding the rRNA16S gene. In total, 20 bacterial strains were identified, belonging to the following genera: Bacillus, Brevibacillus. Brevundimonas, Serratia and Achromobacter. PCR was then performed to characterize the Cry4Ba, Cry11 and BS-glu genes. The results showed that of the 21 lines analyzed, six lines - SPa09, SPa04, 15PHA, BtAM06, R22 and GD 02.13 - presented amplification for the Cry4Ba gene. Considering the BS-glu gene, two strains - SBC2 and standard strain Bti001- amplified for said gene. In the evaluation of the larvicidal activity the quantitative bioassays with 21 strains of bacilli against Ae. aegypti. The results of the quantitative bioassays showed that seven lines were promising in the bacterial biomass assays, where five - R22ISP2, GDO2.13NA, BtAM06, BtAM49LB and SPa09NA - presented 100% mortality in all concentrations - 133 mg / L, 66.6 mg / L, 33.3 mg / L, 16.6 mg / L, 8.33 mg / L and 4.16 mg / L in 24 hours of exposure. The same result was observed for the standard strain Bti001 - B. thuringiensis which showed 100% mortality at all concentrations tested. In the assay with autoclaved biomass, only the R22 line showed 90 to 100% mortality in 72 hours of exposure. In this way, the results of this work provide relevant information about the larvicidal potential of strains of isolated bacilli from different Amazonian environments, which can be used in biological control actions of Ae. aegypti.